El Derecho Del Público a Saber Es El Derecho a Vivir - Camacho Azurduy, Carlos Alberto (Re-presentaciones: Periodismo, comunicación y sociedad, 2007)
According to the author of this text, the access to information is a Human Right protected by international agreements. This implies that information becomes necessary either to create opinion or for steady, well-grounded public debate. Notwithstanding, the simple existence of such a right doesn't necessarily implies an automatic, unconditional and boundless access to it
Keywords: Right to information; Access to information; Habeas Data